Development of a benchmarking framework to assist educationists and schools on sharing strategies and application of best practices : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Engineering at Massey University, Manawatu, New Zealand - Malik, Rubab (Massey University, 2019)
Benchmarking is used by organisations for comparing performance and for the learning and implementation of best practices. While benchmarking remains a widely recognised improvement tool for practitioners, its application by school systems and schools still remains to be investigated. In this research, an exploratory pragmatic multiphase mixed methods research approach is adopted to investigate the use of benchmarking by school systems and schools. Through the preliminary literature review, school systems and schools were recognised to be using benchmarking informally without being aware of its application. Further research showed that informal benchmarking brought improvements to school systems and schools. It is envisaged that school systems and schools can obtain greater improvements through the systematic use of benchmarking. Therefore, a benchmarking framework has been developed to assist school systems and schools in the planning and application of benchmarking. At the start of the research, a preliminary conceptual model of effective benchmarking was developed and this model has guided the research methodology. Then, a literature review was conducted to validate the use of benchmarking by school systems and schools. Next, a quantitative-qualitative survey was administered to school systems (n = 20) and schools (n = 183) to determine the frequency of benchmarking used by school systems and schools and its contribution to their performance, along with an identification of the benchmarking techniques used. The survey also recognised school systems and schools obtaining effective performance through benchmarking. Subsequently, qualitative structured interviews were conducted with these school systems (n = 4) and schools (n = 19) for an exploration of their benchmarking techniques and success factors. Finally, findings from all three phases of the research were integrated to develop a benchmarking framework to assist school systems and schools in the planning and application of benchmarking for the learning and implementation of best practices. The theoretical contributions of the research include the acknowledgement of use of benchmarking by school systems and schools and the confirmation of the association between benchmarking and performance improvement. The practical contribution is the Benchmarking Framework developed to assist school systems and schools in the application of benchmarking approaches and to guide them in the identification and implementation of best practices. Finally, the limitations and future research opportunities have been outlined. One of the most significant research opportunities is to apply the Benchmarking Framework for an actual benchmarking project for the learning and implementation of best practices.
Keywords: School improvement programs; School management and organization; Benchmarking (Management); 350714 Public sector organisation and management